2021
DOI: 10.3389/fpsyg.2021.769424
|View full text |Cite
|
Sign up to set email alerts
|

The Predictability of Chinese English as a Foreign Language Students’ Willingness to Communicate Through Teachers’ Immediacy and Teacher–Student Rapport

Abstract: The teacher–learner relationship is not just a simple action and reaction on both sides of the relationship but a complete exchange that takes shape in the context of the factors that affect it. To understand the factors affecting this relationship, the present study investigated the predictability of Chinese English as a Foreign Language (EFL) students’ willingness to communicate (WTC) through teachers’ immediacy and teacher–student rapport. To conduct the study, 858 EFL students from Xinyang Normal Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 67 publications
(93 reference statements)
1
8
0
Order By: Relevance
“…So far, a plethora of research has been undertaken to delve into the impact of teacher-student rapport on students and their academic behaviors (e.g., Frisby and Housley Gaffney, 2015;Quin, 2017;Henry and Thorsen, 2018;Snijders et al, 2020;Thornberg et al, 2020;Cai, 2021;Li and Yang, 2021;Noble et al, 2021). For example, Thornberg et al (2020) explored the effect of teacher-student rapport on students' involvement.…”
Section: Teacher-student Rapportmentioning
confidence: 99%
See 3 more Smart Citations
“…So far, a plethora of research has been undertaken to delve into the impact of teacher-student rapport on students and their academic behaviors (e.g., Frisby and Housley Gaffney, 2015;Quin, 2017;Henry and Thorsen, 2018;Snijders et al, 2020;Thornberg et al, 2020;Cai, 2021;Li and Yang, 2021;Noble et al, 2021). For example, Thornberg et al (2020) explored the effect of teacher-student rapport on students' involvement.…”
Section: Teacher-student Rapportmentioning
confidence: 99%
“…The results showed that Chinese students viewed teacher-student rapport as a strong predictor of their self-efficacy. More recently, Cai (2021) assessed the role of teacher-student rapport in predicting Chinese students' L2WTC. In doing so, 858 university students were invited to answer two pre-developed questionnaires.…”
Section: Teacher-student Rapportmentioning
confidence: 99%
See 2 more Smart Citations
“…The former speaks about all the activities which are performed by the teachers. Providing the learners with immediate feedback, carrying on conversations before and after classes while guiding the learners through the conversations are some to mention which consequently result in improving learners' motivation and their involvement (Cai, 2021). The latter refers to the teachers' attitude toward their students and how they can minimize their physical and psychological distances with their students and how well they can build up a friendly relationship with them.…”
Section: Introductionmentioning
confidence: 99%